Accounting for social risk factors in Medicare payment : data (Online access: NCBI NCBI Bookshelf., 2016)
Recent health care payment reforms aim to improve the alignment of Medicare payment strategies with goals to improve the quality of care provided, patient experiences with health care, and health outcomes, while also controlling costs. These efforts move Medicare away from the volume-based payment of traditional fee-for-service models and toward value-based purchasing, in which cost control is an explicit goal in addition to clinical and quality goals. Specific payment strategies include pay-for-performance and other quality incentive programs that tie financial rewards and sanctions to the quality and efficiency of care provided and accountable care organizations in which health care providers are held accountable for both the quality and cost of the care they deliver. Accounting For Social Risk Factors in Medicare Payment: Data is the fourth in a series of five brief reports that aim to inform ASPE analyses that account for social risk factors in Medicare payment programs mandated through the IMPACT Act. This report provides guidance on data sources for and strategies to collect data on indicators of social risk factors that could be accounted for Medicare quality measurement and payment programs.